Air source heat pump assisted drying for food applications : a mini review - Budžaki, Sandra (Array, 2019)
Drying as one of the oldest food preservation processes is also the most energy demanding process. Nowadays, when conventional energy sources are declining, reduction/rationalization of energy consumptions in industrial processes is of great importance. One of the more successful ways of saving energy and make the process energy efficient is the integration of heat pumps within the existing technological processes. Heat pump systems are successfully used for different applications such as heating and cooling, and drying as well. In addition, the quality of final dried product is a priority that can be accomplished by heat pump assisted drying systems. This paper presents up-to-date survey in the field of air source heat pump assisted drying of food: fruit, vegetables, herbs and spices.